STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) METHOD AS A TOOL TO IMPROVE STUDENT LEARNING OUTCOME OF CHRISTIAN RELIGION - Alex Frans Nathanael Nasution; Anastasia Runesi; Pamungkas Adi Nugroho (Diegesis : Jurnal Teologi, 2022)
The purpose of this study was to determine the increase in learning outcomes of Christian Religious Education for students of Class X SMA Negeri 84 West Jakarta through the implementation of cooperative learning type Student Teams Achievement Division (STAD). Using the classroom action research method, this research is directly involved in the classroom action process. Researchers act as teachers to teach and assess student learning outcomes. This study consisted of the initial conditions of 2 meetings, the first cycle of 4 meetings, and the second cycle of 2 meetings. The sample set was 18 students of class X to practice eight times. From the results of tests that researchers have carried out, it can see that the STAD method can successfully influence student learning outcomes such as: (i) In the initial conditions of the first meeting, the average score of students is 76 & the value of completeness of student learning outcomes is 75 while the score is not complete is 60, (ii) Then the first cycle is the fourth meeting the average value of students is 82 and the value is included in the excellent category and has a learning completeness value is 92 & (iii) the last show's cycle II is the ninth meeting the overall average value of students is 90 and is included in the excellent category and has a learning completeness value of 100%.